2014
DOI: 10.1097/qai.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Concentrations in Small Hair Samples as a Feasible Marker of Adherence in Rural Kenya

Abstract: Antiretroviral hair levels objectively quantify drug exposure over time and predict virologic responses. We assessed the acceptability and feasibility of collecting small hair samples in a rural Kenyan cohort. 95% of participants (354/373) donated hair. Although median self-reported adherence was 100% (IQR 96–100%), a wide range of hair concentrations likely indicates overestimation of self-reported adherence and the advantages of a pharmacologic adherence measure. Higher nevirapine (NVP) hair concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 42 publications
7
100
1
Order By: Relevance
“…In our study, the acceptability of hair collection was high (100%), which is consistent with prior studies by our group in Africa showing high rates of feasibility and acceptability (>95%) in hair collection. 8,12 Hair collection for exposure monitoring may be particularly desirable in pediatric populations, since hair sampling avoids phlebotomy. 24 However, we have shown that early implementation of community information campaigns and field staff training are important to enhance hair collection rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the acceptability of hair collection was high (100%), which is consistent with prior studies by our group in Africa showing high rates of feasibility and acceptability (>95%) in hair collection. 8,12 Hair collection for exposure monitoring may be particularly desirable in pediatric populations, since hair sampling avoids phlebotomy. 24 However, we have shown that early implementation of community information campaigns and field staff training are important to enhance hair collection rates.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 Approximately 20 strands of hair (1-3 mg) are required to measure the concentration of most ARVs. 13,14 Hair samples were cut from underneath the top layer of hair from the occiput 8,9 and then subsequently placed in aluminum foil, stored at room temperature, and shipped to the University of California, San Francisco (UCSF) for analysis.…”
Section: Hair Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from rural Kenya showed that community information campaigns and field staff training early in protocol development was likely to enhance hair collection rates [14]. A qualitative study from South Africa on the acceptability of hair collection underscored this point [15].…”
Section: Discussionmentioning
confidence: 99%
“…Hair collection has been shown to be feasible and acceptable (>95%) among HIV-infected or at-risk individuals in Africa [3,14]. A recent study from rural Kenya showed that community information campaigns and field staff training early in protocol development was likely to enhance hair collection rates [14].…”
Section: Discussionmentioning
confidence: 99%